Higher levels of cardiovascular fitness are associated with better executive function and prefrontal oxygenation in younger and older women - Dupuy, Olivier; Gauthier, Claudine J.; Fraser, Sarah A.; Desjardins-Crèpeau, Laurence; Desjardins, Michèle; Mekary, Said; Lesage, Frederic; Hoge, Rick D.; Pouliot, Philippe; Bherer, Louis (Frontiers in Human Neuroscience, 2015)
Aim: Many studies have suggested that physical exercise training improves cognition and more selectively executive functions. There is a growing interest to clarify the neurophysiological mechanisms that underlie this effect. The aim of the current study was to evaluate the neurophysiological changes in cerebral oxygenation associated with physical fitness level and executive functions. Method: In this study, 22 younger and 36 older women underwent a maximal graded continuous test (i.e., O2max) in order to classifyassign them into a fitness group (higher vs. lower fit). All participants completed neuropsychological paper and pencil testing and a computerized Stroop task (which contained executive and non-executive conditions) in which the change in pPrefrontal cortex oxygenation change was evaluated in all participants with a near infrared spectroscopy (NIRS). system during a computerized Stroop task (which contains executive and non-executive conditions). Results: Our findings revealed a Fitness x Condition interaction (p < .05) such that higher fit women scored better on measures of executive functions than lower fit women. In comparison to lower fit women, higher fit women had faster reaction times in the switching (executive)Executive condition of the computerized Stroop task. No significant effect was observed ion the non-executive condition of the test and no interactions were found with age. In measures of cerebral oxygenation (ΔHbT and ΔHbO2), we found a main effect of fitness on cerebral oxygenation during the Stroop task such that only high fit women demonstrated a significant increase in the right inferior frontal gyrus. Discussion/Conclusion: Higher fit individuals who demonstrate better cardiorespiratory functions (as measured by O2max) show faster reaction times and greater cerebral oxygenation in the right inferior frontal gyrus than women with lower fitness levels. The lack of interaction with age, suggests that good cardiorespiratory functions